2010
DOI: 10.1063/1.3182831
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacity of Liquids: Critical Review and Recommended Values. Supplement II

Abstract: A study was carried out in which new experimental data on heat capacities of pure liquid organic and some inorganic compounds were compiled and critically evaluated and recommended values provided. The bulk of the compiled data covers data published in the primary literature between 2000 and 2006 and includes some data published in 2007. However, some data from older sources are also included. The list of compound families covered was extended to include ionic liquids. Parameters of correlating equations for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 654 publications
1
77
0
1
Order By: Relevance
“…29 (N = 4, 6, 8, 10, 12). 30 The decrease in the 2 ] is mainly due to the decrease of the ionic liquid densities along the alkyl chain length of the cation. 29 The observed constant value for the C o p /V for the heavier symmetrical ionic liquids probably results from a balance between the decrease of the density and the increase of the contribution per methylene group, −CH 2 −, in the volumic heat capacities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 (N = 4, 6, 8, 10, 12). 30 The decrease in the 2 ] is mainly due to the decrease of the ionic liquid densities along the alkyl chain length of the cation. 29 The observed constant value for the C o p /V for the heavier symmetrical ionic liquids probably results from a balance between the decrease of the density and the increase of the contribution per methylene group, −CH 2 −, in the volumic heat capacities.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate heat capacity data have a wide field of application in thermochemistry for calculating changes in reaction enthalpies and in chemical engineering for establishing energy balances. [1][2][3] The possible use of ionic liquids (ILs) as heat transfer for heat exchange in chemical plants and solar thermal power generation was discussed, and it was found that the imidazolium based ionic liquids present higher heat capacities per unit of volume that two high performance commercial thermal fluids. [4][5][6] The knowledge of the heat capacity is required for the evaluation of the applicability of the ionic liquids as heat transfer fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Because the experimental data are presented permanently, it is necessary to update database of critically assessed and recommended data. Therefore authors´s work has been also aimed at updating and extending two publications prepared earlier within the framework of the IUPAC projects (Zábranský et al, 1996;Zábranský et al, 2001). These publications contain recommended data on liquid heat capacities for almost 2000 mostly organic compounds expressed in terms of parameters of correlating equations for temperature dependence of heat capacity.…”
Section: Liquid Heat Capacitymentioning
confidence: 99%
“…These publications contain recommended data on liquid heat capacities for almost 2000 mostly organic compounds expressed in terms of parameters of correlating equations for temperature dependence of heat capacity. In new work (Zábranský et al, 2010b) Altogether new data for almost 500 compounds, out of them about 250 compounds were not covered the in previous works (Zábranský et al, 1996;Zábranský et al, 2001), were compiled and critically evaluated.…”
Section: Liquid Heat Capacitymentioning
confidence: 99%
See 1 more Smart Citation